Longitudinal Differences in Cognitive Functioning Among Older Adults With and Without Heart Failure. (December 2013) - Alwerdt, Jessie; Edwards, Jerri D.; Athilingam, Ponrathi; O'Connor, Melissa L.; Valdés, Elise G.
Objective: Secondary data analyses were conducted to examine cognitive function and longitudinal cognitive decline among older adults with and without heart failure (HF).Method: Data from the Advanced Cognitive Training for Independent and Vital Elderly study were used to compare baseline ( N = 2, 790) and longitudinal ( n = 692) changes in memory, reasoning, and speed of processing performance among participants ( M age = 73.61, SD = 5.89) who self-reported HF at baseline, developed HF over time, or never reported HF.Results: At baseline, there were differences in memory and speed of processing with participants who never reported HF performing better than those who reported developing HF over time, and those who reported HF at baseline performing the worst ( p s < .05). Longitudinally, participants with self-reported HF at baseline showed declines in reasoning over time.Discussion: The results indicate that cognitive difficulties in memory and speed may occur prior to a HF diagnosis, while those with HF may experience steeper declines in reasoning as measured by word series test.